Public health and burnout: a survey on lifestyle changes among workers in the healthcare sector - Petrelli, Fabio; Scuri, Stefania; Tanzi, Elisabetta; Nguyen, Cuc; Grappasonni, Iolanda (Acta Biomedica Atenei Parmensis, 2018)
Burnout Syndrome is a condition which could most commonly be associated with negative effects on the quality of work and life. Some occupations are more likely to suffer from this syndrome, for example workers in the health sector. This survey was therefore conducted among hospital workers of the Marche Region in order to analyze levels of Burnout and any possible correlation of these levels with lifestyle changes. Methods: The survey was carried out using a self-administered, anonymous questionnaire in two sections: the first consisted of the Maslach Burnout Inventory (MBI) and the second contained questions about the healthcare operator’s lifestyle. The MBI investigates levels of Emotional Exhaustion (EE), Depersonalization (DP) and finally of Personal Accomplishment (RP) in respondents. Survey results were processed using descriptive statistics, applying the Chi-square statistic and an Odds Ratio (p<0.05). Results: 53.4% of the questionnaire was duly completed. The scale with the highest incidence among interviewees was Depersonalization. Even though the high-level percentage for the DP and EE scale was equal to 22.3%, when adding the high-level percentage to the medium level percentage, the difference between low and medium-high level was found to be around 20% for all areas. Analyzing the correlation between lifestyle choices, and in particular the consumption of alcohol and smoking with Burnout Syndrome, a statistically significant Odds Ratio was observed in the DP scale vs alcohol (OR=4.67), the RP scale vs cigarette smoke (OR=2.50), and finally in the EE area vs cigarette smoke (OR=2.92). Conclusion: Our results are in line with other studies which show increasing levels of EE and DP in healthcare workers. Healthcare workers who have been in the same job for a considerable amount of time (15+ years) show the highest levels of EE and DP. Subjects with high levels of Depersonalization show a worrying exposure to alcohol abuse, while those with high levels of Emotional Exhaustion tend to make use of both alcohol and tobacco, demonstrating negative lifestyle choices; in spite of this, results for personal accomplishment being relatively low and therefore not cause for worry, subjects still show high levels of exposure to cigarette smoke.